Percepções dos Profissionais da atenção Básica Sobre o Serviço de Atendimento Móvel de Urgência de Belo Horizonte - Renata Lacerda Prata Rocha (2009)
Healthcare in Brazil has been through changes and adaptations to meet the health needs of the population, as a result of the increased demand, especially for urgent and emergency care. Given the fact that early care for the health of people and social groups in emergency situations reduces illness, handicap, chronic suffering and early death, among others, it became clear that there is a need to organize urgent and emergency care in the country at all levels. This organization was facilitated with the establishment, in 2003, of the National Policy for Emergency Care, including its pre-hospital ambulance component, the EmergencyMobile Care Service (in Portuguese, SAMU: a public ambulance system). SAMU is part of a regional and hierarchically organized network for emergency care which receives calls from the public and health workers in situations of emergency from different parts of town. Very little study has been done on this service, if compared to the emergency wards of large hospitals that have existed for much longer. This study intends to analyze the perception of health workers in basic care on the work carried out by SAMU, considering the influence of the actions on the work dynamics of the Basic Health Care Units (in Portuguese, UBS). Aqualitative case study was carried out in a USB in Belo Horizonte, State of Minas Gerais, Brazil . The data was collected through semi-structured interviews with 22 health workers and content analysis was carried out. Analyzing the data it was possible to identify three categories: 1) The integration between Basic Health Care Units and the Emergency Mobile Care Service, which was subdivided into the sub-categories: 1.1)Work in basic health care and emergency situations and 1.2)The Perception of basic health care workers about SAMU; 2) Relations between health workers in basic health care and SAMU and 3) The future outlook of the relation between basic health care and SAMU from the point of view of health workers. The results show that primary health care workers have a positive view of the work carried out by SAMU, from the point of view of professional qualification for urgency/emergency care, availability of resources and speed in providing care. The data show, on the other hand, little coordination between the two services, which weakens therelationship between basic health care and SAMU. They also show there are conflicts, a transfer of responsibility in accepting judgment of urgency situations by both parties and some resentment at the positive view of the population toward SAMU and not so positive for the work of basic health care. This situation is related to the referrals criteria, especially ofpatients in acute cases, the definition of roles and responsibilities, infrastructure and professional training for caring for urgencies. In summary, the statements by basic health care workers show a situation of recognition and denial of SAMU, as occurs in other healthservices and other levels where there is not always unanimity. The services are supplementary, there is recognition of the competence and importance of SAMU for the population of Belo Horizonte, but work is still done without coordination, assistance is therefore fragmented and results in difficulties for both basic health care and SAMU healthworkers.